Pengaruh Asimetri Informasi, Ukuran Perusahaan dan Kepemilikan Manajerial Terhadap Manajemen Laba - Silviana Setiawati; Syaiful Syaiful (Journal of Culture Accounting and Auditing, 2022)
This study aims to determine the effect of information asymmetry, firm size and managerial ownership on earnings management. This research uses quantitative research. The data analysis technique used descriptive statistical analysis, data quality test and hypothesis testing. Earnings management variable is measured using Discretionary Accruals, information asymmetry is measured by bid-ask spread, firm size is measured using the natural logarithm of total assets, managerial ownership is measured by the percentage comparison of the number of managers' shares with the number of shares outstanding in the company. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. Sampling was done by purposive sampling method, with a total sample of 237 data. The results of this study indicate that information asymmetry has no effect on earnings management, while firm size and managerial ownership have a negative and significant effect on earnings management.